2019
DOI: 10.1093/treephys/tpz078
|View full text |Cite
|
Sign up to set email alerts
|

The stability enigma of hydraulic vulnerability curves: addressing the link between hydraulic conductivity and drought-induced embolism

Abstract: Maintaining xylem water transport under drought is vital for plants, but xylem failure does occur when drought-induced embolisms form and progressively spread through the xylem. The hydraulic method is widely considered the gold standard to quantify drought-induced xylem embolism. The method determines hydraulic conductivity (Kh) in cut branch samples, dehydrated to specific drought levels, by pushing water through them. The technique is widely considered for its reliable Kh measurements, but there is some unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…Although the bench dehydration technique is labour‐intensive, it is regarded as the most reliable hydraulic technique for measurement of cavitation resistance and provides a direct measure of impacts on hydraulic conductance. Even so, we note that a number of sources of experimental error have been identified with the bench dehydration method, including those associated with excision of plant material (Wheeler et al ., 2013) and measurement of xylem flow rates on the bench (Espino & Schenk, 2011; De Baerdemaeker et al ., 2019). In this context, the close agreement between hydraulic methodology and in situ visual techniques suggests that all techniques tested here produce reliable estimates of cavitation resistance if the appropriate precautions are taken.…”
Section: Discussionmentioning
confidence: 99%
“…Although the bench dehydration technique is labour‐intensive, it is regarded as the most reliable hydraulic technique for measurement of cavitation resistance and provides a direct measure of impacts on hydraulic conductance. Even so, we note that a number of sources of experimental error have been identified with the bench dehydration method, including those associated with excision of plant material (Wheeler et al ., 2013) and measurement of xylem flow rates on the bench (Espino & Schenk, 2011; De Baerdemaeker et al ., 2019). In this context, the close agreement between hydraulic methodology and in situ visual techniques suggests that all techniques tested here produce reliable estimates of cavitation resistance if the appropriate precautions are taken.…”
Section: Discussionmentioning
confidence: 99%
“…The datasets generated for this study can be found in the Github https://github.com/Pneumatron. (Sperry et al, 1988;Bréda et al, 1993;Wheeler et al, 2013;De Baerdemaeker et al, 2019;Bonetti et al, 2020) Centrifuge self-construction is technically highly challenging; hydraulic artefacts; destructive (Alder et al, 1997;Cochard et al, 2005;Torres-Ruiz et al, 2014Wang et al, 2014;Peng et al, 2019) Air and not straightforward (Milburn and Johnson, 1966;Tyree et al, 1984;Nolf et al, (Hochberg et al, 2016;Bouda et al, 2019)…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Observations of embolism could also be hampered by artifacts associated with hydraulic conductivity measurements, such as bubble formation by cutting of xylem under negative pressure, and artificial refilling of embolized conduits (Wheeler et al, 2013;De Baerdemaeker et al, 2019). For this reason, nonintrusive methods provide a welcoming alternative to visualize the hydraulic status of xylem conduits in vivo.…”
Section: Introductionmentioning
confidence: 99%